2022
DOI: 10.1186/s12913-022-07852-3
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction in midwives and its association with organisational and psychosocial factors at work: a nation-wide, cross-sectional study

Abstract: Background Midwives report a challenging work environment globally, with high levels of burnout, insufficient work resources and low job satisfaction. The primary objective of this study was to identify factors in the organisational and psychosocial work environment associated with midwives’ job satisfaction. A secondary objective was to identify differences in how midwives assess the organisational and psychosocial work environment compared to Swedish benchmarks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 40 publications
2
13
1
2
Order By: Relevance
“…In turn, Iranian research reports that a lack of job satisfaction has a significant negative impact on the quality of communication and patient care [ 43 ]. Swedish midwives, when assessing job satisfaction, emphasized the lack of professional recognition instead, drawing attention to the perceived conflict of roles and the feeling of burnout [ 44 ]. A Polish study of 350 nurses and midwives indicated that the average burnout rate was 34.7 per 100 points, and the most important factor related to burnout was emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, Iranian research reports that a lack of job satisfaction has a significant negative impact on the quality of communication and patient care [ 43 ]. Swedish midwives, when assessing job satisfaction, emphasized the lack of professional recognition instead, drawing attention to the perceived conflict of roles and the feeling of burnout [ 44 ]. A Polish study of 350 nurses and midwives indicated that the average burnout rate was 34.7 per 100 points, and the most important factor related to burnout was emotional exhaustion.…”
Section: Discussionmentioning
confidence: 99%
“…Leadership-as-practice is less about what one person does and is more about what can be accomplished by a collective, through day-to-day experiences [ 37 ]. Managers that contribute to a collective leadership demonstrate that the midwives are valued, encouraging their involvement in decision-making, thereby improving job satisfaction [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Managers are pivotal to the workplace culture and to the wellbeing of their staff, in turn reflecting on the care women and families receive [ 52 ]. The current crisis of the retention of midwives in the profession, calls for the managers’ workload to be taken seriously to enable them to support midwives to be healthy, happy and to stay in midwifery [ 10 , 12 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations